California girls [large type] - Mallery, Susan (Thorndike Press, a part of Gale, a Cengage Company, 2019)
Mria's Synopsis: The California sunshine's not quite so bright for three sisters who get dumped in the same week... Finola, a popular LA morning-show host, is famously upbeat until she's blindsided on live TV by the news that her husband is sleeping with a young pop sensation who has set their affair to music. While avoiding the tabloids and pretending she's just fine, she's crumbling inside, desperate for him to come to his senses and for life to go back to normal. Zennie's breakup is no big loss. Although the world insists she pair up, she'd rather be surfing. So agreeing to be the surrogate for her best friend is a no-brainer--after all, she has an available womb and no other attachments to worry about. Except...when everyone else, including her big sister, thinks she's making a huge mistake, being pregnant is a lot lonelier--and more complicated--than she imagined. Never the tallest, thinnest or prettiest sister, Ali is used to being overlooked, but when her fiancé sends his disapproving brother to call off the wedding, it's a new low. And yet Daniel continues to turn up "for support," making Ali wonder if maybe--for once--someone sees her in a way no one ever has. But side by side by side, these sisters will start over and rebuild their lives with all the affection, charm and laugh-out-loud humor that is classic Susan Mallery.